Corrosion resistance and protective properties of chromium coatings electrodeposited from an electrolyte based on deep eutectic solvent - Protsenko, V.S.; Bobrova, L.S.; Korniy, S.A.; Kityk, A.A.; Danilov, F.I. (Functional Materials, 2018)
The paper deals with the corrosion resistance and protective properties of chromium coatings electrodeposited from an electrolyte based on deep eutectic solvent, a new generation of ionic liquids. The electroplating bath contained chromium (III) chloride, choline chloride and some extra water. Chromium layers with a thickness of 2.5, 5, 10, 15 and 20 μm were deposited on mild steel samples and their corrosion and electrochemical behavior was determined by voltammetry method and electrochemical impedance spectroscopy technique. It was stated that the highest resistance to corrosion damage of the Cr layer and mild steel substrate is achieved when the thickness of deposit is about 5 μm. At smaller or greater thickness, the chromium electrodeposits become more defective, and a larger number of microcracks and micropores appear; as a result, the corrosion stability and protective characteristics diminish.